Neural Profiling of Brands: Mapping Brand Image in Consumers' Brains with Visual Templates. (August 2018) - Chan, Hang-Yee; Boksem, Maarten; Smidts, Ale
The authors demonstrate a novel template-based approach to profiling brand image using functional magnetic resonance imaging. They compare consumers' brain responses during passive viewing of visual templates (photos depicting various social scenarios) and brain responses during active visualizing of a brand's image, and then they generate individual neural profiles of brand image that correlate with the participant's own self-report perception of those consumer brands. In aggregate, these neural profiles of brand image are associated with perceived cobranding suitability and reflect brand image strength rated by a separate and bigger sample of consumers. This neural profiling approach offers a customizable tool for inspecting and comparing brand-specific mental associations, both across brands and across consumers. It also demonstrates the potential of using pattern analysis of neuroimaging data to study multisensory, nonverbal consumer knowledge and experience.